The Panorama (1837-1868): history of a journal - SANT’ANNA, Benedita de Cássia Lima (2007)
The Panorama was thrown in Lisbon, on May 6, 1837, for the Spread Society of Useful Knowledge, founded, on that same year, with the exclusive purpose of publishing a periodical of content varied, literary and instructive that goes well I accept for all the classes of citizens. Considered the paradigm of the Portuguese Romantic press, with him begins and he closes the Romantic movement in Portugal. Our objective in this text is to contemplate about the publication of that periodical, to identify the most important aspects than they involve your project production, your graphic presentation, editor's transfer (proprietor), as well as to present to the researcher and studious of the literary press of Portuguese language a reading about the publication of that important periodical.